O acesso e a permanência de alunos com deficiência visual na escola - Silva, Carla Esthefane Souza da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work aims to verify how is the access and continuity of students with disabilities, specifically, students with visual impairment in school. The main purpose, it seeks to understand visual impairment by addressing themes such as: definition, type and characteristic; and through the analysis of the historical path of laws and decrees destined to inclusive education guaranteed by various instances of power, including outside the Brazilian sphere. Methodologically, this is a qualitative research, in which, following this aspect, the present study was carried out through the integration between documentary, bibliographic and field researches of exploratory nature in which the knowledge resulting from the literature studied concerning the aforementioned research, served as the basis for the formulation of our research instrument for data collection , which were two structured questionnaires with open questions, respectively, sent to the Teaching Supervisor - Special Learning of the Board of Education - Guaratinguetá Region and the schools that are part of the Board of Directors in which there are visually impaired students enrolled. Therefore, the analysis of the data of this research showed that, even though there is the right to education, the access and the permanence of this student at school are ensured by law, in a certain way, there is still an arduous path to be followed, in order to make the educational process more equitable and less different to the visually impaired student and the seer.

O presente trabalho tem por objetivo verificar como é o acesso e a permanência dos alunos com deficiência, especificamente, educandos com deficiência visual na escola. Para tal, busca compreender a deficiência visual abordando temas, como: definição, tipo e característica; e por meio da análise do percurso histórico de leis e decretos destinados à educação inclusiva garantidos por variadas instâncias de poder, inclusive fora da esfera brasileira. Metodologicamente, trata-se de uma pesquisa de caráter qualitativo, em que seguindo essa vertente, o presente estudo realizou-se através da integração entre a pesquisa documental, a pesquisa bibliográfica e a pesquisa de campo de natureza exploratória em que o conhecimento decorrente das literaturas estudadas concernentes às pesquisas supracitadas, serviu de base para a formulação de nosso instrumento de pesquisa para a coleta de dados, os quais foram dois questionários estruturados com perguntas abertas, respectivamente, enviados à Supervisora de Ensino – Educação Especial da Diretoria de Ensino – Região de Guaratinguetá e as escolas que integram a Diretoria em que há alunos deficientes visuais matriculados. Portanto a análise dos dados desta pesquisa mostrou que, por mais que o direito à educação ao acesso e a permanência desse aluno sejam assegurados por lei, de certo modo, há ainda um árduo caminho a ser percorrido, a fim de tornar o processo educacional mais equitativo e menos díspar ao educando com deficiência visual e ao vidente.
Access and permanence of students with visual impairments in school
Keywords: Visual Impairment; Inclusive Education; Access and Permanence in school; Deficiência Visual; Educação Inclusiva; Acesso e Permanência na Escola; Deficientes visuais – Educação; Deficientes visuais – Orientação e mobilidade; Educação especial; Processo de aprendizagem